Social Interaction With Relapsed Partner Facilitates Cocaine Relapse in Rats - Meng, Shiqiu; Yan, Wei; Liu, Xiaoxing; Gong, Yimiao; Tian, Shanshan; Wu, Ping; Sun, Yan; Shi, Jie; Lu, Lin; Yuan, Kai; Xue, Yanxue (Frontiers in Pharmacology, 2021)
Social factors strongly contribute to drug use and relapse, and epidemiological studies have found that members of peer groups influence each other to use drugs. However, previous animal models mostly failed to incorporate social factors and demonstrate the effects of social partners on drug addiction and relapse. In the present study, we investigated the transfer of relapse to cocaine seeking between drug-addicted partners in rats. Male Sprague–Dawley rats were pair-housed and subjected to training and extinction of cocaine self-administration and conditioned place preference (CPP). 24 h after extinction test, the targeted rats interacted with a cocaine-primed (relapsed) partner or stranger, or saline-injected (unrelapsed) partner for 30 min, after which the targeted rats were tested for drug seeking behavior. We found that social interaction with a relapsed partner increased drug seeking behavior in cocaine self-administration and CPP models in rats, while social interaction with an unrelapsed partner or relapsed stranger had no effect on cocaine seeking. Moreover, the effect of social interaction on cocaine seeking could last for at least 1 day. Our findings demonstrate a facilitation effect of relapsed social partners on drug relapse in rats and provide a novel animal model for social transfer of drug relapse.